Single‐Crystalline Zn(002) Facet Enables Ultrastable Anode–Electrolyte Interface - Tao Shen; Tingting Wei; Shuxian Zhang; Heng Liu; Changyuan Li; Zhaoqian Li; Menghao Yang; Chaofeng Liu; Yanzhong Pei (Small Structures)
Dendrite growth and detrimental parasitic side reactions at the anode–electrolyte interface severely restrain the reversibility and cyclability of aqueous zinc‐ion batteries. Due to the lowest surface energy in Zn metal with a hexagonal close‐packed structure, (002) facet can effectively alleviate these side effects. In contrast to several existing works on (002) texturization, single‐crystalline Zn successfully grown using a Bridgman method in this work offers a fundamental understanding on this issue. The perfect atomic arrangement of the low‐surface‐energy (002) cleavage planes, without any grain boundaries, not only kinetically enables an epitaxial deposition inhibiting dendrite formation but also thermodynamically endows the most stable state restraining the side reactions. As a result, the single‐crystalline Zn(002) anode demonstrates a cycling stability over 4800 h (6.7 month) at 2 mA cm−2 in symmetric batteries. Zn(002)//Cu asymmetric batteries achieve a high average Coulombic efficiency of 99.92% over 500 cycles at 10 mA cm−2, enabling a fundamental demonstration of interface engineering for advancing batteries.